Study on the size effect of elastic modulus of rock considering the joint spacing - Zhao, Tao; Hu, Gaojian (Frontiers in Materials, 2023)
The elastic modulus reflects the deformation characteristics of rock, which is affected by joint spacing and joint ductility, but the relationship has not been obtained. In this paper, the size effect of elastic modulus of rock with parallel joints is studied by numerical simulation and regression analysis. The results show that there is an exponential relationship between the elastic modulus and the spacing of parallel joints, and a negative exponential relationship between the elastic modulus and the size of rock; The characteristic size of elastic modulus has a power function relationship with the spacing of parallel joints, and the characteristic elastic modulus of rock has a power function relationship with the spacing of parallel joints. The general and specific forms of these relations are given. The establishment of these relations has realized the prediction and calculation of the elastic modulus of the mine rock mass, and provided guidance for the deformation analysis of the rock.